Functional and genomic characterization of Komagataeibacter uvaceti FXV3, a multiple stress resistant bacterium producing increased levels of cellulose - Nascimento, Francisco X. (2022)
Bacterial cellulose is one of the most promising biomaterials for the development of a wide array of novel biotechnological solutions. Nevertheless, the commercial production of bacterial cellulose is still a challenge and obtaining novel strains presenting increased cellulose biosynthesis and stress resistance properties is of extreme importance. This work demonstrates the increased stress resistance, cellulose production abilities, and overall genomic properties of Komagataeibacter uvaceti FXV3, a novel cellulose-producing and stress resistant strain isolated from a fermented grape must. K. uvaceti FXV3 was able to grow under several stress conditions, including the presence of high concentrations of ethanol (up to 7.5 % v/v), a trait that is not observed in the model strain K. xylinus CECT 7351T. Moreover, K. uvaceti FXV3 produced increased concentrations of cellulose (4.31 mg/mL, 7 days after inoculation-DAI) when compared to K. xylinus CECT 7351T (1.42 mg/mL, 7 DAI). Moreover, the detailed analysis of strain FXV3 genome revealed the presence of several genes involved in cellulose and acetan biosynthesis, quorum-sensing and quenching mechanisms, carbohydrate, amino acid, alcohol and aldehyde metabolism, as well as several other genes involved in stress resistance. Additionally, comparative genomic analysis revealed the increased prevalence of stress resistance genes in K. uvaceti FXV3 when compared to K. xylinus CECT 7351T. Ultimately, this study reveals the increased biotechnological potential of K. uvaceti FXV3 and brings new insights into the genetics behind Komagataeibacter stress resistance and cellulose production abilities.